2016
DOI: 10.1038/srep25098
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantification of CWD Prions in Fixed Paraffin Embedded Tissues by Real-Time Quaking-Induced Conversion

Abstract: Traditional diagnostic detection of chronic wasting disease (CWD) relies on immunodetection of misfolded CWD prion protein (PrPCWD) by western blotting, ELISA, or immunohistochemistry (IHC). These techniques require separate sample collections (frozen and fixed) which may result in discrepancies due to variation in prion tissue distribution and assay sensitivities that limit detection especially in early and subclinical infections. Here, we harness the power of real-time quaking induced conversion (RT-QuIC) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 30 publications
3
38
0
Order By: Relevance
“…30 In the current study, the next earliest time point was 30 dpi; thus, arrival of misfolded prion protein was between 30 and 60 dpi. Because the retina is spatially distinct from the brain, where the inoculum was delivered, we are confident that the seeding activity detected is a result of transport, presumably retrograde transport via the optic nerve 31 ; however, here we cannot entirely rule out transport by the circulatory system, as infectious prion protein was likely in blood of these animals before its detection in retina.…”
Section: Prion Seeding Activity Is Detected In the Retina Relativelymentioning
confidence: 64%
“…30 In the current study, the next earliest time point was 30 dpi; thus, arrival of misfolded prion protein was between 30 and 60 dpi. Because the retina is spatially distinct from the brain, where the inoculum was delivered, we are confident that the seeding activity detected is a result of transport, presumably retrograde transport via the optic nerve 31 ; however, here we cannot entirely rule out transport by the circulatory system, as infectious prion protein was likely in blood of these animals before its detection in retina.…”
Section: Prion Seeding Activity Is Detected In the Retina Relativelymentioning
confidence: 64%
“…RT-QuIC provides a rapid methodology for analysis of tissues and fluids containing minute quantities of prions (85,86) and may have utility in quantitative and correlative investigations of early and carrier states of prion diseases and potentially other protein misfolding disorders (86)(87)(88)(89). There is little to no evidence that RT-QuIC generates, or represents, the presence of prion infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have compared RT-QuIC seeding activity to CWD cervid brain in a 50% lethal dose (LD 50 ) bioassay (88,94). Because we used the same conditions and controls for this study, we applied this principle to our RT-QuIC data.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments performed during development of the FPE RT-QuIC method demonstrated that RT-QuIC amyloid seeding was achieved at higher seed concentrations of fixed paraffin-embedded (FPE) samples than had been previously reported using conventional frozen brain to prepare homogenates (15). Amyloid seeding in FPE brain-derived samples had a linear detection range extending from 10 Ϫ1 to 10 Ϫ7 , whereas non-FPE frozen brain homogenate samples displayed a linear range extending from 10 Ϫ4 to 10 Ϫ8 , likely due to inhibitors at high concentrations and consistent with published literature (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Through the development of methods to detect prion-seeding activity in fixed paraffin-embedded tissues using RT-QuIC (FPE RT-QuIC), we were able to detect amyloid-seeding activity at higher sample concentrations, 10 Ϫ1 and 10 Ϫ2 dilutions, than previously possible for brain homogenates (15). We then endeavored to identify the components of brain homogenate responsible for inhibiting the RT-QuIC amyloid formation reaction.…”
mentioning
confidence: 99%